12c-39=7c-74

Simple and best practice solution for 12c-39=7c-74 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12c-39=7c-74 equation:


Simplifying
12c + -39 = 7c + -74

Reorder the terms:
-39 + 12c = 7c + -74

Reorder the terms:
-39 + 12c = -74 + 7c

Solving
-39 + 12c = -74 + 7c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-7c' to each side of the equation.
-39 + 12c + -7c = -74 + 7c + -7c

Combine like terms: 12c + -7c = 5c
-39 + 5c = -74 + 7c + -7c

Combine like terms: 7c + -7c = 0
-39 + 5c = -74 + 0
-39 + 5c = -74

Add '39' to each side of the equation.
-39 + 39 + 5c = -74 + 39

Combine like terms: -39 + 39 = 0
0 + 5c = -74 + 39
5c = -74 + 39

Combine like terms: -74 + 39 = -35
5c = -35

Divide each side by '5'.
c = -7

Simplifying
c = -7

See similar equations:

| (5x-1)=(7x-23) | | 2x+B-7=56 | | 7d+8=2d+18 | | 1/3w-3/2=-5/7 | | x²-11/x-4 | | 9j-5=3j-5 | | -28.3x^3+3.09x^2+262.3=0 | | 8b-32=3b-62 | | 5n+1=25 | | 100-x/5000=10x | | 6e-36=e-71 | | 4(x-2)-3(x-1)=8x-10 | | 2a^2*a^2=360 | | 20-x/3=x2 | | 8f-1=6f+1 | | 9t-17=4t-32 | | 9t-17-4t-3= | | 5x-1=2x-23 | | 14/3x14/3 | | .10x+0.35(50)=22.5 | | 6u-26=2u-50 | | X=x-2000 | | 2(x-7)+7=4x-(2x+4)-3 | | 10-p+9=12 | | 5c+3=13+3x | | -x=--3/4 | | A=52cm^2 | | 4(w-2)=9 | | 7-2(2x+4)-3x+8=-2-2x-6x | | 50=.73x | | 6/0.142 | | f(x)=7x+6 |

Equations solver categories